(untitled) (Revista Espinhaço, 2024)
The municipality of Ladainha, located in the Immediate Geographic Region of Teófilo Otoni-MG, was for decades one of the main logistical warehouses of the Estrada de Ferro Bahia e Minas, a railway that has great importance in the imaginary of the population of the Jequitinhonha, Mucuri valleys and extreme south of Bahia, even though its tracks were torn up in 1966. Supported by documentary sources, analysis of demographic and socioeconomic data, and interviews with a group of Ladainhense railway workers who experienced the operational end of the “Bahiminas,” this study presents a geo-historical characterization and an analysis of the changes brought to the urban landscape by the arrival of the railway. Additionally, it reflects on the “last train,” which metaphorically led hundreds of Ladainhenses into the unknown following the line’s closure in the region. Subsequently, the research evaluates the economic and demographic stagnation of the municipality during the post-railway period, a phenomenon that still impacts the local landscape today. Finally, the study highlights the need to revisit the historical and social effects of the railway’s deactivation to understand the current dynamics of decline, which left deep marks on the railway workers and the local population, evoking topophobic feelings and negatively influencing the collective perception of the city’s future.